Integrated oral microbiome and metabolome analysis unveils key biomarkers and functional pathway alterations in patients with acute myocardial infarction - Ikram Khan; Muhammad Irfan; Imran Khan; Xie Ping; Yu Xiaohui; Shengnan Lei; Tianzhu Song; Xiaodong Xie; Zhiqiang Li (Frontiers in Cellular and Infection Microbiology)
IntroductionThe significance of oral microbiota in acute myocardial infarction (AMI) has been increasingly appreciated. However, the association between oral microbiota, metabolites, and AMI parameters, as well as the key microbiota and metabolites that may play a crucial role in this process, remains unclear. To investigate the oral microbiome composition and metabolomic profiles associated with AMI and explore the roles of specific bacterial species and key metabolites in functional pathways in the progression of AMI.MethodsA case-control study was conducted involving 24 AMI patients and 24 matched healthy controls. Saliva samples were collected for 16S rRNA sequencing and untargeted LC-MS metabolomics. Correlation analysis was then performed to explore associations between microbial taxa, metabolomic profiles, and AMI clinical parameters, with results visualized as heatmaps of correlation coefficients.ResultsThe component of the oral microbiota of the AMI group showed significant alterations when compared to the control group. Particularly, a significant shift in terms of alpha and beta diversity was observed between the AMI and control groups (p < 0.05). The Streptococcus and Rothia genera, as well as 9(R)-HODE, 20-HETE ethanolamide, and 5,6 EET metabolites, were identified as potential biomarkers, achieving an area under the curve of 0.82–0.88. Functional pathway analysis demonstrated significant upregulation in key metabolic pathways, including the Citrate Cycle (TCA cycle), Pyruvate metabolism, and Glucagon signaling pathways, which exhibited strong correlations with established clinical markers of AMI.ConclusionThis integrative analysis underscores the diagnostic potential of oral microbiome-metabolome interactions in AMI and unveils key mechanistic pathways for guiding future therapeutic interventions.